Meta-Analysis of the Effect of Cognitive Conflict on Physics Learning - Fatni Mufit; Asrizal Asrizal; Reni Puspitasari (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2020)
Problems often experienced by students in learning physics are misconceptions and low understanding of concepts. One solution to this problem is to apply conflict cognitive learning. The purpose of this study was to analyze: (1) the problems that lead to the application of cognitive conflict learning, especially in physics learning, (2) the stages of cognitive conflict learning that are often used, (3) the effect of cognitive conflict learning on education levels, (4) the effect of cognitive conflict learning on eye lessons, and (5) the effect of cognitive conflict learning on learning competencies. This study uses a meta-analysis method, namely analyzing similar scientific article documents. The sample consisted of 25 national and international articles published in 2012-2020. Data analysis used the effect size equation, percentage techniques, and descriptive analysis. The results and findings of the study indicate: (1) The problems that often cause cognitive conflict learning to be applied to physics learning are poor understanding of concepts and misconceptions, (2) Learning conflict cognitive has different stages, but the most widely used consists of three main steps, (3) Cognitive conflict learning has a high effect on being applied in high school, (4) high effect cognitive conflict learning is applied to physics lessons, and (5) Learning conflict cognitive has a high influence in increasing understanding of concepts and overcoming misconceptions, especially physics. This study indicates that cognitive conflict learning has a good influence in overcoming conceptual understanding problems, especially in learning physics in high school.